Qualitative Analysis with MAXQDA: Effect of HRM Practices on Organization Performance with Mediation of Employees' Work Attitude in Textile Industries of Ethiopia - Metasebia Adula; Shashi Kant; Zerihun Ayenew Birbirsa (RSF Press, 2023)
Businesses cannot ignore the critical issue of employee work attitude since it affects how committed both current employees and recruits are to the company. It is now simpler to access many resources, especially with the advancement of technology. However, locating motivated human resources has never been as simple. Now that motivated individuals have been found, performance appraisal to, and worked with for a while, a critical role has been assigned to employee commitment. In this vein, the study's goal is to look into how HRM procedures help recruit individuals to the company for job openings. The study employed content analysis, a qualitative analytical technique. The results of this investigation were made accessible using the MAXQDA 2020 software tool. The study outcomes revealed a significant overlap in the usage of employee commitment and human resource management ideas. The study's findings have led to a better understanding of how organizations can use employee commitment and effective external rewards to attract motivated workers. It has been observed that this contact helps the business selection, which has been crucial in raising the company's visibility, favorability, and dependability.